2002
DOI: 10.1016/s0886-3350(01)01257-3
|View full text |Cite
|
Sign up to set email alerts
|

Laser-assisted deep sclerectomy

Abstract: Deep sclerectomy using the Er:YAG laser was safe and effective in eyes with OAG. More studies are needed to analyze the mechanism of lowering IOP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
1
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 18 publications
0
15
1
1
Order By: Relevance
“…Others reported 5-FU injection rates between 6 and 50%. 8,13,14,16 The number of YAG-goniopunctures performed in our study is lower compared to published data, 16,19,24 which might be owing to the exact dissection with the laser, resulting in a very thin TDM.…”
Section: Discussioncontrasting
confidence: 60%
See 4 more Smart Citations
“…Others reported 5-FU injection rates between 6 and 50%. 8,13,14,16 The number of YAG-goniopunctures performed in our study is lower compared to published data, 16,19,24 which might be owing to the exact dissection with the laser, resulting in a very thin TDM.…”
Section: Discussioncontrasting
confidence: 60%
“…The rate of choroidal detachment, hyphema, and shallowing of the anterior chamber is comparable to the data in the literature (range: 0-33%). 11,13,14,17,23 Average preoperative BCVA was low in our study group, as two patients had poor visual fields, two patients developed cataracts and pre-existing cataracts progressed in another four patients. Other studies with a long-term follow-up have shown similar cataract progression rates compared to our study.…”
Section: Discussionmentioning
confidence: 59%
See 3 more Smart Citations